Effects of thermal cycles and immersion in different beverages on color, translucency and hardness of different composite resins - Ömer Sağsöz; Pınar Gül (Selcuk Dental Journal)
The aim of this study is to evaluate the color stability, translucency and hardness of eight different composite resins, after thermal cycling and immersion in beverages. Six light-cured dimethacrylate-based composite (Clearfil Majesty Esthetic, Clearfil Majesty Posterior, Grandio, Grandio Flow, Arabesk Top, Valux Plus), an ormocer (Admira) and a silorane-based composite (Filtek Silorane) were tested in this study. Fifteen samples (8x2 mm) from each composite were prepared. All samples were subjected to thermal cycling [(5.0 ± 0.5)~(55.0 ± 1.0) °C, 1000 cycles]. After thermal cycling, fifteen specimens in each group were divided into three subgroups (n = 5): distilled water (control), coffee, and red wine at 37°C for 30 days. With a spectrophotometer, the △E and Translucency Parameter (TP) were calculated against white and black backgrounds. Color, translucency and hardness of all samples were remeasured baseline, after thermal cycles and after immersion in beverages. The data were analyzed using repeated measured analysis of variance and Bonferroni multiple-comparison test (P3.3). The effect of thermal cycles on color and transluceny was not statistically significant (P>0.05). TP values generally decreased especially after immersion in red wine (P